2003
DOI: 10.1073/pnas.0330962100
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolipin regulates sarco(endo)plasmic reticulum Ca 2+ -ATPase (SERCA) by binding to transmembrane helices alone or in association with phospholamban

Abstract: S arco(endo)plasmic reticulum Ca 2ϩ -ATPases (SERCAs) are 110-kDa membrane proteins that catalyze the ATPdependent transport of Ca 2ϩ from the cytosol to the lumen of the sarco(endo)plasmic reticulum (1). SERCAs expressed in muscle are regulated by two members of a gene family: phospholamban (PLN) (2, 3) and sarcolipin (SLN) (4-6).PLN is a 52-aa membrane protein that interacts with SERCA molecules to lower their apparent affinity for Ca 2ϩ and inhibit their activity at low, but not at high, Ca 2ϩ concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
152
3
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(165 citation statements)
references
References 30 publications
9
152
3
1
Order By: Relevance
“…However, the same study shows that when coexpressed with SERCA, C-terminus of SLN is not needed for its retention in the ER suggesting that C-terminus may have a different function [23]. The flexible nature of the C-terminus also leaves Tyr-29 and Tyr-31 residues available for interactions with various aromatic residues in the transmembrane helices of SERCA and suggests that lumenal domain could be involved in the regulation of SERCA-SLN interaction [20,21,23].…”
Section: Sarcolipin Is Structurally Similar To Plbmentioning
confidence: 97%
See 4 more Smart Citations
“…However, the same study shows that when coexpressed with SERCA, C-terminus of SLN is not needed for its retention in the ER suggesting that C-terminus may have a different function [23]. The flexible nature of the C-terminus also leaves Tyr-29 and Tyr-31 residues available for interactions with various aromatic residues in the transmembrane helices of SERCA and suggests that lumenal domain could be involved in the regulation of SERCA-SLN interaction [20,21,23].…”
Section: Sarcolipin Is Structurally Similar To Plbmentioning
confidence: 97%
“…Co-immunoprecipitation studies have shown that SLN can interact with SERCA2a. SLN can bind SERCA either alone or in association with PLB [21]. Biochemical data and structural modeling using NMR suggest that both SLN and PLB bind SERCA in the same molecular groove and with similar mechanisms [19,20].…”
Section: Independent Inhibition Of Serca2a and Could Contribute For Tmentioning
confidence: 97%
See 3 more Smart Citations